(untitled) (Tzintzun, Revista de Estudios Históricos, 2016)
Cholera was one of the illnesses that provoked the greatest death rates in the world during the eighteenth century. In Mexico, the states of Chiapas, Tabasco and Oaxaca were the most affected during the period from 1882-1883, and the people of Michoacan suffered the effects of this illness in 1833 and 1850. In times when the possibility of cholera infection in the country or state alarmed the authorities of Mexico and Michoacan each evaluated specific necessary personal and public hygiene measures, and these were elaborated with the help of medical institutions. In case of the epidemics of 1833 and 1850, the sanitary politics in Michoacan were demonstrated in new laws and with the dissemination of curative methods designed by the Protomedicato and the Faculty of Medicine and their approved by the state government